Metode Komunikasi Kesehatan Relawan Surveilans dalam Edukasi Covid-19 Pada Masa Endemi - Nurhaipah, Titih Nurhaipah; Erdiyanti, Yucky Putri (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
Abstract The corona virus outbreak has infected humans in almost every country in the world. Information on this virus is still under development and research continues. Some countries have even exploded in cases like Indonesia. The role of surveillance volunteers is to help process data and communicate to educate about the virus. Therefore, health communication in the community must be done using different methods. However, the purpose of health communication is effectively achieved. This research was conducted using qualitative research methods, in which there is no purpose for generalization. The results of this study include that health communication or, in this case, health promotion is important. The important role of health communication carried out by volunteers is to transmit accurately and uniformly. Since this information must be able to touch the community with steps that were taken inadvertently, the persuasion or health communication was done by volunteers as part of the community itself. There are health communication methods implemented by surveillance volunteers to educate the public about Covid-19, including 1) health communication through an individual approach; 2) health communication through the puskesmas team; and 3) health communication through social media. In addition, there is a flow of information in health communication activities, that is, the information that is processed in the communication process and therefore there is a coordination that can validate the information before it is finally published in the current media and health information is consumed by the public.Keywords: Health Communication, Volunteers, Covid-19